Isotretinoin‐associated intracranial hypertension: A concise report - Kanya Rani Vashisht; Sachin Varma; Mahtab Yeganegi (Wiley, 2024)
Abstract We present a case of a 24‐year‐old preobese female undergoing isotretinoin treatment for acne vulgaris, who experienced drug‐induced intracranial hypertension (DIIH). Recognizing and addressing this potentially serious adverse effect is essential to prevent severe outcomes, particularly irreversible vision impairment. When suspected, immediate discontinuation of isotretinoin, neuroradiological imaging and urgent ophthalmologic evaluation to rule out papilloedema is imperative. Formulation of alternative treatment strategies, caution while prescribing DIIH‐causing drugs in future patient treatments and proactive reporting of adverse events are integral aspects of its comprehensive management.